Analisis Residu Herbisida dalam Pengendalian Gulma Berdaun Lebar Di Savana Bekol Taman Nasional Baluran - Saputri, Rinny; Ratnadewi, YM Diah; Tjitrosoedirdjo, Soekisman; Setyawati, Titiek (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2023)
The research was conducted in the savanna Bekol - Baluran National Park, East Java to find the best rate of herbicide to control broadleaved weeds in the savanna and to estimate the soil residue of herbicide used. The experimental design was a randomized block with six treatments and four replications. The treatments were herbicide applications consisted of (1) the rate of triclopyr at 670 g a.i ha-1 (TA), (2) rate of triclopyr at 1340 a.i ha-1 (TB), (3) the rate of fluroxypyr at 200 g a.i ha-1 (FA), (4) rate of fluroxypir at 400 g a.i ha-1 (FB), (5) Weeding Manual (PM) and (6) Control (K). The application of triclopyr at 670 g ai ha-1 was among the best of treatments applied. Sampling of soil at day 0 and day 28 after application indicated the residue of triclopyr 670 g ai ha-1 was 0.16 ppm and DT50 = 14 d.